PERENCANAAN JALAN TANDING MARGA – SEI DUA KABUPATEN PENUKAL ABAB LEMATANG ILIR - Agustina, Resti; Suprapto, Bhakti Yudho; Bochori; Natassia, Karina; Akhirini, Akhirini (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
Roads are one of the means of land transportation and will continue to develop as one of the transportation infrastructures to meet the needs of the community in carrying out various activities. Road development is one of the things that continues to experience progress in terms of technology and the mindset of the people who use it, so that roads are an important place for the community. Jalan Tanding Marga to SEI Dua, Karang Tanding Village, North Penukal District is also a frequently used access road where the current condition still does not have a pavement construction so that planning is needed for the geometry and type of pavement. The research method carried out through several stages, namely topographic surveys, investigations of existing conditions, geometric planning of roads in the Geometric Planning Procedures for Roads issued by the Directorate General of Highways No.038/BM/1997 and determination of the thickness of the road pavement according to SNI 03-1732-1989. The results of the study showed that the design speed plan was 40 km/hour which met the technical requirements. The results of the analysis show that the recommended types of flexible pavement layers can use the AC-Base, AC-BC and AC-WC types with thicknesses of 150 mm, 60 mm and 40 mm respectively.